Does unmet health care lead to poorer health outcomes? - Bataineh, Hana; Devlin, Rose Anne; Barham, Vicky (Université d'Ottawa | University of Ottawa, 2018)
Using the National Population Health Survey, a nationally representative longitudinal data set spanning 16 years, we analyze if the presence of perceived unmet health-care (UHC) needs affects health outcomes paying close attention to the potential endogeneity of this problem. Five different health-related outcomes are examined. We find clear and robust evidence that the presence of UHC either two-years previously or anytime in the past, affects negatively the current health of the individual – controlling for a host of other influences. The age of the individual does not affect this relationship.
Keywords: unmet health care; health outcomes; instrumental variables; medications use